If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + -2) + -5(-2x + -5) = 18(x + -1) + -6 Reorder the terms: 9(-2 + x) + -5(-2x + -5) = 18(x + -1) + -6 (-2 * 9 + x * 9) + -5(-2x + -5) = 18(x + -1) + -6 (-18 + 9x) + -5(-2x + -5) = 18(x + -1) + -6 Reorder the terms: -18 + 9x + -5(-5 + -2x) = 18(x + -1) + -6 -18 + 9x + (-5 * -5 + -2x * -5) = 18(x + -1) + -6 -18 + 9x + (25 + 10x) = 18(x + -1) + -6 Reorder the terms: -18 + 25 + 9x + 10x = 18(x + -1) + -6 Combine like terms: -18 + 25 = 7 7 + 9x + 10x = 18(x + -1) + -6 Combine like terms: 9x + 10x = 19x 7 + 19x = 18(x + -1) + -6 Reorder the terms: 7 + 19x = 18(-1 + x) + -6 7 + 19x = (-1 * 18 + x * 18) + -6 7 + 19x = (-18 + 18x) + -6 Reorder the terms: 7 + 19x = -18 + -6 + 18x Combine like terms: -18 + -6 = -24 7 + 19x = -24 + 18x Solving 7 + 19x = -24 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 7 + 19x + -18x = -24 + 18x + -18x Combine like terms: 19x + -18x = 1x 7 + 1x = -24 + 18x + -18x Combine like terms: 18x + -18x = 0 7 + 1x = -24 + 0 7 + 1x = -24 Add '-7' to each side of the equation. 7 + -7 + 1x = -24 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = -24 + -7 1x = -24 + -7 Combine like terms: -24 + -7 = -31 1x = -31 Divide each side by '1'. x = -31 Simplifying x = -31
| -6-9-5*5= | | 5(5)+(6)=8 | | 7-7z=35 | | 12x=-3x | | 3x-5y=41-6x | | x^2-4x+11=0 | | s+1.5=0.8 | | 3(v-1)=6v-4 | | B(12+b)-7=2b+b(-4+b) | | 13x*2+5x+1=0 | | 2x+5-x=9-x+2 | | 1=0.4-0.6x-5 | | -8*-3+3*4= | | 2-3y=-8 | | -9(x-2)=-10x | | 31-17= | | 5x-18-4*x=-36 | | -9(x-2)+18=-10x | | -(3y-6)+10= | | 4+2(-x+2)=26 | | 25.33*x+.5*(-7.5)*x^2=4.4*x | | f+4/8=6 | | 13=4x+3(x-5) | | 4*7+9*-2= | | 6(3x-1)-18= | | 4c+21c+27=0 | | 3(9a+4b)-8(a+8b)=0 | | -5(4q+2)=-3q+10 | | r=-20+10a | | -3*-8-9= | | 3=4(x+3)-5 | | -79+12x=38+3x |